A Review of Formulation Techniques and Evaluation Parameters of Fast Dissolving Tablets: Review Article (Journal of Pharma Insights and Research, 2024)
Fast dissolving tablets (FDTs) have gained significant popularity as a convenient and patient-friendly dosage form, particularly beneficial for pediatric, geriatric, and patients with swallowing difficulties. These tablets are formulated to disintegrate or dissolve rapidly in the oral cavity, eliminating the need for water and enhancing patient compliance. This review article provides a comprehensive overview of FDTs, covering various aspects such as their definition, ideal characteristics, advantages, and formulation techniques. The manufacturing methods employed in the development of FDTs are discussed in detail, including direct compression, lyophilization, tablet molding, mass extrusion, spray drying, nanotization, sublimation, and the cotton candy process. Special emphasis is placed on the critical role of superdisintegrants, such as croscarmellose sodium, crospovidone, and sodium starch glycolate, in achieving rapid disintegration of the tablets. The review also highlights the essential pre-compression and post-compression evaluation parameters for FDTs, ensuring their quality and performance. These parameters include angle of repose, bulk density, tapped density, compressibility index, Hausner's ratio, tablet hardness, thickness, friability, drug content uniformity, weight variation, wetting time, water absorption ratio, in-vitro disintegration time, and in-vitro dissolution studies. The advantages of FDTs include patient compliance, rapid onset of action, increased bioavailability, and improved stability